First record of the genus Orochernes (Pseudoscorpiones: Chernetidae) from China, with description of a new species - Gao, Zhizhong; Zhang, Feng (Zootaxa, 2019)
The chernetid genus Orochernes Beier, 1968 is reported from China for the first time. Orochernes ganziensis sp. n. is described from the Sichuan Province and characterized through illustrations and genetic data. The spermathecae of the genus Orochernes are illustrated for the first time.